Transcendental a priori and conventional a priori. The devious path of apriority from Kant to Putnam - Melogno, Pablo (Analysis. Journal of Philosophical Research, 2018)
In several works produced in the 60's and 70's, Putnam introduced the notion ofcontextually a priori, trying to give an account of the principles that fix the limitsof the possible experience within a conceptual scheme. According to Putnam, theseprinciples are originated by the satisfaction of specific cognitive needs, and not byconventional stipulations. This paper discusses the putnamian notion of the a prioriin relation to the stances of Poincaré, Reichenbach and Carnap, trying to establishin each case the points of convergence with the putnamian conception, as well asthe reasons that led Putnam to reject the conventionalist views of the a priori. Itis argued that the putnamian account can be considered as a rehabilitation of thetranscendental component of the Kantian a priori, as for Putnam the a priori principlesare not only constitutive of the objects, but they fix cognitive limits that can only beovercome in contexts of conceptual change.